Plant breeding reviews. Volume 36 (Wiley Blackwell, 2012)
Plant Breeding Reviews presents state-of-the-art reviews on plant breeding and genetics covering horticultural, agronomic and forestry crops, incorporating both traditional and molecular methods. The contributions are authored by world authorities, anonymously reviewed, and edited by Professor Jules Janick of Purdue University, USA. The series is an indispensible resource for crop breeders, plant scientists, and teachers involved in crop improvement and genetic resources